Schooling and National Income: How Large Are the Externalities? (2007)
This paper uses a new data set for cumulative national investment in formal schooling and a newinstrument for schooling to estimate the national return on investment in 61 countries. These estimates are combined with data on the private rate of return on investment in schooling to estimate the external rate of return. In 1990 the external rate of return ranged from 10 percent in high-income countries to over 50 percent in the lowest-income countries. The external benefits of schooling are about equal to the private benefits in high-income countries and three times the private benefits in the lowest income countries.